2021
DOI: 10.1111/voxs.12614
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude, and perception towards voluntary blood donation among university students in Nigeria

Abstract: Background Adequate provision of safe blood through voluntary non-remunerated donation (VNRD) is critical to the delivery of quality health care. Understanding the factors affecting blood donation and addressing them would lead to an improvement in blood donation in Africa. The objective of this study was to determine factors affecting VNRD among culturally diverse Nigerian students.Methods In this cross-sectional descriptive study, 840 students were selected by a stratified random sampling technique and given… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Female donors were found to be 39 percent [23] and 40 percent [24] lower in Nigeria and Ethiopia, respectively. Female donors account for barely 5% of all donors in Iran [25].…”
Section: Discussionmentioning
confidence: 91%
“…Female donors were found to be 39 percent [23] and 40 percent [24] lower in Nigeria and Ethiopia, respectively. Female donors account for barely 5% of all donors in Iran [25].…”
Section: Discussionmentioning
confidence: 91%
“…The knowledge of blood donation has been consistently shown to be an important factor that determines blood donation practices across different populations. A study across different faculties of discipline among undergraduate university students in Nigeria showed that students from the college of medicine had significantly better knowledge and higher donation rate compared with other students from humanities, law, sciences, and engineering (Ogundeji et al, 2021) and this was similar to the finding of Gebresilase et al, (2017) and Nwabueze et al, (2014). However, Nwogoh et al, (2013) in Benin found a disparity between knowledge, attitude, and actual donation practice among health workers (9).…”
Section: Introductionmentioning
confidence: 81%